(untitled) (Hekima Review, 2010)
The dogs and cats sit around the fireplace Light pierce the dark night Drums sing the old songs, Muffled, the song drown in darkness Red eyes tears from the smoke drops. Words roll from the silenced drums. Words, words, words, a muffled nipple.